2021
DOI: 10.2106/jbjs.rvw.20.00096
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chronic Quadriceps Tendon Rupture

Abstract: » Chronic quadriceps tendon (QT) ruptures are uncommon injuries that present treatment challenges due to their complex nature and the limited evidence to guide management.» Timely diagnosis and surgical management of acute QT injury are imperative to optimize patient outcomes as delayed diagnosis leads to poorer results regardless of treatment modality.» Elements of chronic QT ruptures that may complicate surgical management include patient age, comorbidity, scar-tissue formation, amount of quadriceps muscle/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 38 publications
(130 reference statements)
0
29
0
Order By: Relevance
“…While ruptures of other tendons (Table 5), such as the flexor digitorum profundus and superficialis tendons, require swift intervention because of the prompt retraction of the tendon stumps, in extensor tendons, such as the triceps brachii and quadriceps tendon, retraction is slower, and usually can be treated acutely with direct repair [27]. Recently, a systematic review about chronic QTRs suggested that the timing of surgical intervention plays a crucial role in the functional outcomes, setting the cutoff for early treatment at 2-3 weeks from the injury [15]. However, all the articles included in the current study reported acceptable functional outcomes even though the surgery had occurred at least 40 days after the rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While ruptures of other tendons (Table 5), such as the flexor digitorum profundus and superficialis tendons, require swift intervention because of the prompt retraction of the tendon stumps, in extensor tendons, such as the triceps brachii and quadriceps tendon, retraction is slower, and usually can be treated acutely with direct repair [27]. Recently, a systematic review about chronic QTRs suggested that the timing of surgical intervention plays a crucial role in the functional outcomes, setting the cutoff for early treatment at 2-3 weeks from the injury [15]. However, all the articles included in the current study reported acceptable functional outcomes even though the surgery had occurred at least 40 days after the rupture.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used and well described are transosseus sutures and anchors, but it is still unclear which technique offers the best postoperative advantages because of the limited number and quality of available studies [14]. A chronic tendon rupture has typically not been diagnosed or treated for at least 3 weeks [15]. The choice of the best surgical technique can be challenging, and it depends on the macroscopic quality of the tendon stump rather than the timing of intervention [16].…”
Section: Introductionmentioning
confidence: 99%
“…Atraumatic ruptures frequently occur in patients with underlying systemic diseases as well as fluoroquinolone and corticosteroid use. 1 , 2 , 3 The current literature recommends surgical repair within the first 48 to 72 hours to achieve the most successful outcome. Repair of chronic QT ruptures, defined by 3 weeks’ postinjury, has been reported to have worse functional outcomes likely due to scar tissue formation, distal retraction of the patella, quadriceps muscle atrophy, and large tendon gapping.…”
mentioning
confidence: 99%
“…Previously reported techniques include primary repair, tissue lengthening, or advancement with a V-Y plasty and reconstruction with an autograft or allograft. 1 , 2 With the goal of improving functional outcomes in patients with poor tissue quality and not amenable to lengthening techniques, we describe the repair of a chronic QT rupture with an Achilles tendon bone block allograft.…”
mentioning
confidence: 99%
“…1,2 Injuries to the extensor mechanismdincluding quadriceps tendon ruptures, patellar fractures, and patellar tendon rupturesddevastate knee function and limit mobility. 1,3 Marked by significant extensor lag and appreciable suprapatellar defect, quadriceps tendon ruptures must be promptly diagnosed and treated. 4,5 Partial tears can be managed conservatively, including casting with the knee in extension for at least 6 weeks.…”
mentioning
confidence: 99%